Navigating through our history in research: An altmetric analysis for publications by the full-time operative dentistry faculty at the Aga Khan University Hospital in the past decade - Nighat Naved; Fahad Umer (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the social dissemination of the publications by fulltime faculty at a tertiary care facility. Methods: The retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised publication records of the fulltime Operative Dentistry faculty members between July 2011 till July 2021. The search was done on Google Scholar, Altmetric Explorer and PubMed electronic databases. After the final screening, all the publications in PubMed-indexed journals, including in vitro studies, randomised controlled trials, original research articles, case reports and letters to the editor, for which the Altmetric Attention Score was available were included. Results: Of the 225 publications identified, 34 (15%) formed the final sample. The cumulative citation count for the publications was 617 and Altmetric Attention Score was 158. There were 16 Facebook mentions and 163 tweets. Conclusion: The social impact of publications by the Operative Dentistry faculty over a decade was not convincing in terms of Altmetric Attention Score. Continuous...